Rancangan Sistem Informasi Reservasi Dan Pemasaran Barbershop Berbasis Web Untuk Meningkatkan Efisiensi Operasional - Ahmad Haidar; Maulina Mukaromah; Iqbal Ahmad Bukhari; Edy Susena (Switch : Jurnal Sains dan Teknologi Informasi, 2025)
Digitalization demands the MSME sector, including barbershops, to adopt technology in reservation management and marketing. Many barbershops still use manual systems, causing problems such as irregular queues, service delays, and suboptimal promotions. This study formulates how to design an information system that can integrate reservation and marketing functions into a single web-based platform. The objective is to produce an efficient, secure, and user-friendly information system design for both barbershop managers and customers. The method used is the Design Science Research approach with a waterfall system development model, involving needs analysis, system design, database design, and user interface design. The design results were validated by experts and users with a satisfaction rate of over 85%, indicating that the designed system aligns with the operational needs of barbershops. The conclusion is that the developed information system can enhance operational efficiency and customer experience, and is suitable for implementation in the barbershop service sector of SMEs.